Seduhan Daun Kelor (Moringa Oliefera) Untuk Meningkatkan Imunitas Tubuh: Mini Review - Atikah Proverawati; Nuriya Nuriya (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
ABSTRACT Background: The human immune system is influential on a person's tendency to attached the disease. Low immunity conditions allow various microorganisms to grow and to develop, thus causing infectious diseases. High immunity components are useful for fighting microorganisms. Objective: This study aims to examine the role of steeping Moringa Oliefera leaves in increasing body immunity. Methods: The research method used is a mini review of research results published in scientific journals. Journals are obtained from electronic databases such as Google Scholar, PubMed, and Science Direct published from 2011 to 2020, in English, and original articles are not reviews. Results: The results showed that Moringa leaf (Moringa Oliefera) has complete nutritional content, namely iron, protein, vitamin A, vitamin C, potassium and calcium. Moringa leaves can be used as herbal drinks to increase body immunity. The components present in the Moringa leaves steeping work as antioxidants, anti-inflammatory, and immunomodulator. Conclusion: The conclusion is that the steeping of Moringa leaves contains high levels of antioxidants that are useful as immunostimulants.